2011
DOI: 10.3109/00207454.2011.620192
|View full text |Cite
|
Sign up to set email alerts
|

Premotor Symptoms and Early Diagnosis of Parkinson's Disease

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 77 publications
1
17
0
3
Order By: Relevance
“…13, 3032 The current study revealed that BMI was not associated with PD, Prion, FTD, PSP, or CBD after adjusting for confounders such as age. Another hypothesis concerns the hyposmia often observed in prodromal stages of AD; however, early hyposmia is also present in other diseases such as PD, 3336 which did not show any significant association with BMI. The absence of significant relationships between cardiovascular factors and other dementias may support that certain neuropathological features may be sufficient for the development of the dementia.…”
Section: Discussionmentioning
confidence: 98%
“…13, 3032 The current study revealed that BMI was not associated with PD, Prion, FTD, PSP, or CBD after adjusting for confounders such as age. Another hypothesis concerns the hyposmia often observed in prodromal stages of AD; however, early hyposmia is also present in other diseases such as PD, 3336 which did not show any significant association with BMI. The absence of significant relationships between cardiovascular factors and other dementias may support that certain neuropathological features may be sufficient for the development of the dementia.…”
Section: Discussionmentioning
confidence: 98%
“…As olfactory testing is inexpensive compared to the imaging modalities mentioned, an initial screen for hyposmia would appear to make fiscal sense. Identifying at-risk individuals is crucial for improving future symptomatic and disease-modifying treatment studies of PD [12] as well as leading to a better understanding of the neurodegenerative process of PD [1]. …”
Section: Discussionmentioning
confidence: 99%
“…While olfactory dysfunction occurs during normal aging, there are strong data supporting olfactory dysfunction preceding the clinical symptoms of Parkinson's disease (PD), perhaps representing one of the earliest signs of the disease [1,2]. Some data suggest olfactory dysfunction precedes motor findings in PD by up to seven years and recent data also shows olfactory dysfunction is a biomarker in two other synucleinopathies, rapid eye movement (REM) sleep behavior disorder (RBD) [3] and incidental Lewy body disease (ILBD) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of cognitive functions in the PD risk-group may be useful (Adler, 2011), but there are several factors that complicate the search for the cognitive profile of pre-diagnostic PD. First of all, PD itself has a heterogeneous cognitive profile (Svenningsson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%